2014
DOI: 10.1103/physrevb.89.045304
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a localized spin excitation close to the spin-helix regime

Abstract: The time evolution of a local spin excitation in a (001)-confined two-dimensional electron gas subjected to Rashba and Dresselhaus spin-orbit interactions of similar strength is investigated theoretically and compared with experimental data. Specifically, the consequences of the finite spatial extension of the initial spin polarization is studied for non-balanced Rashba and Dresselhaus terms and for finite cubic Dresselhaus spin-orbit interaction. We show that the initial out-of-plane spin polarization evolves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 19 publications
6
35
1
Order By: Relevance
“…Several theoretical studies have identified the cubic Dresselhaus term as the main decay mechanism of the persistent spin helix (Cheng and Wu, 2006;Cheng et al, 2007;Kettemann, 2007;Kurosawa et al, 2015;Liu and Sinova, 2012;Lüffe et al, 2011;Lusakowski et al, 2003;Shen and Wu, 2009;Wenk and Kettemann, 2011), in accordance with experiments already mentioned (Koralek et al, 2009;Salis et al, 2014).…”
Section: Stability Of the Spin Helix: Limiting Factorssupporting
confidence: 74%
See 1 more Smart Citation
“…Several theoretical studies have identified the cubic Dresselhaus term as the main decay mechanism of the persistent spin helix (Cheng and Wu, 2006;Cheng et al, 2007;Kettemann, 2007;Kurosawa et al, 2015;Liu and Sinova, 2012;Lüffe et al, 2011;Lusakowski et al, 2003;Shen and Wu, 2009;Wenk and Kettemann, 2011), in accordance with experiments already mentioned (Koralek et al, 2009;Salis et al, 2014).…”
Section: Stability Of the Spin Helix: Limiting Factorssupporting
confidence: 74%
“…Effective semiclassical diffusion equations for s( r, t) can be derived via quantum kinetic equations rooted in the Keldysh formalism (Mishchenko et al, 2004). Working in Fourier space at small frequencies and wave vectors, and evaluating the arising parameters within the zero-temperature ground state, one obtains in the regime of weak spin-orbit coupling (Bernevig et al, 2006;Liu and Sinova, 2012;Salis et al, 2014;Stanescu and Galitski, 2007)…”
Section: Spin Diffusion Equationsmentioning
confidence: 99%
“…Nevertheless, we can estimate values for α by taking into account the information contained in the measured values of τ . Assuming a Dyakonov Perel spin relaxation mechanism [22,23] In conclusion, we have demonstrated pump-probe based all-optical measurements of SOI in low-band-gap InGaAs QWs. The SOI is found to be of Rashba type with an upper limit for the coefficient α of 2×10 −12 eVm.…”
mentioning
confidence: 75%
“…If we assume that 2DEG spins, or spins that diffuse over the region illuminated by the pump, are involved in the observed KR signal, the Gaussian spin density profile will initially expand with a speed determined by D s . Because of this expansion, the upper limit of the KR decay constant at early times will be determined by a prefactor 33…”
Section: Discussionmentioning
confidence: 99%